Evaluation of Risk Factors of Acute Pancreatitis among Young Adults in a Tertiary Care Hospital (Journal of Surgical Sciences, 2022)
Background: Acute pancreatitis (AP) is a common gastrointestinal emergency worldwide requiring hospitalization, with an increasing burden on patients and society. Gallstones/sludge and alcohol consumption are the leading causes, while other factors include abdominal trauma, post-ERCP, surgeries, metabolic disorders, hypertriglyceridemia, infections, and certain medications. The aim of the study was to explore the risk factors of acute pancreatitis among young adults.Methods: A Prospective Observational study in tertiary level hospital. Sample was selected from the population by purposive sampling technique. Sample size was 100. Detail demographic data were collected from the subject and recorded in structured case report form. Clinical examination and relevant investigation were done meticulously. All the information recorded in data collection sheet. All collected questionnaire checked very carefully to identify the error in the data. Data processing work was consisted of registration schedules, editing computerization, preparation of dummy table, analyzing and matching of data. Data was processed and analyzed with the help of computer program SPSS and Microsoft excel.Result: Present study demonstrates that maximum number of patients (43.0%) were between 31-35 years age group, mean age of the patient was 36.9 ± 6.7 years. Out of 100 cases 78% were male and 22% were female. Male and female ratio was 3.54:1. In this study physical inactivity had predisposing factor, noted in 39% subjects, followed by sedentary habit in 21% subjects. In this study it was found that 78% of patients were smoker, H/O Gallstone disease were 8 patients, and only 12 patients had history of instrumentation. Drinking alcohol was reported in 5%, all of them were males. H/O diabetes mellitus were in 19.0% subject and dyslipidemia detected in 24.0% patients. Present study demonstrated that, prevalence of obesity is 46.0% patients.Conclusion: The present study showed that sedentary lifestyle, obesity, alcohol, and tobacco are key risk factors for acute pancreatitis among young adults. Helps guide appropriate management and prevent recurrence.    Journal of Surgical Sciences 2022;26(2): 73-77